会话分析研究 ： “like” 在新加坡华语中的语用功能 = Conversation analysis : “like” in Singapore Mandarin conversations - 陈珠凤 Tan, Kyu Houng (2018)
在新加坡特殊的多语环境下，新加坡人的日常会话中经常参杂了多种语言，如英语、华语、马来语、方言以及Singlish的外来词都可在同一段会话中出现。“Like” 虽然是个英文词，但在年轻新加坡人的华语会话中的使用频率较高。“Like” 在英语中有动词、介词和连词的用法，不过近几年的语言发展趋势已让 “like” 的运用出现了话语标记的功能。用语者将“like”的用法延伸至新加坡华语中，造成新加坡华语中使用 “like” 的普遍现象。在频繁使用的过程中，“like” 在某些语境中出现语义弱化的现象，在原本语义的使用上有了语用功能上的扩展。 研究结果显示，“like” 在新加坡华语会话中的不同语境中可作不同的话语标记，担任话语中的不同语用功能：（一）“like” 作为回应开头单位，让说话者示意获取话轮，补充说明相关话题；（二）“like” 作为委婉情态标记，是说话者为了保护形象而使用的委婉情态标记；（三）“like” 作为会话中的停顿填充词，是说话者向听话者示意自己在思考，话轮并未结束；（四）“like” 作为解释说明标记，在说话者要进行解释或说明时预示听话者，让信息传递更顺利；（五）“like” 作为话语修补标记，让听话者语辨认说话者在会话中的话语改正，从而让听话者更快速地处理听到话语中的信息；（六）“like” 作为引用话语标记，让说话者在引用他人的话时，能大致概括他们所说的话，无需逐字逐句引述。 Under Singapore’s unique multilingual environment, many different languages, such as English, Chinese, Malay, dialects, and Singlish slangs could be heard in the daily conversations of Singaporeans. Although “like” is an English word, its usage frequency is high amongst young Singaporeans’ Mandarin conversations. Despite “like” having the usage of verb, preposition and conjunction, the language development trends in the recent years have caused function of “like” in conversations to transit towards that of a discourse marker. Language users have brought its usage into Mandarin, causing the trend of high usage of “like” in Mandarin conversations. Through the process of the high frequency usage, there have been extensions in discourse functions of “like” aside from its original semantic meaning. Results show that “like” take on different discourse functions in different Mandarin conversation contexts: (1) turn-initial object of a response, allowing listeners to take their turn in the conversation by elaborating on an existing topic; (2) a pragmatic hedge with the role of a face-saving device for the speaker (3) filler indicator (4) explanation marker (5) repair marker (6) quotation complement.